Management of Medical Emergencies in the Dental Setting; Laryngospasm - Badhe, Ashok M. (International Journal Of Drug Research And Dental Science, 2023)
Laryngospasm is a common complication in the dental setting. Although it can be self-limited in some cases, if it persists and goes untreated it may be life-threatening and cause serious complications. While it is more common in the oral surgery setting it may also occur while under the care of a general dentist. This article discusses laryngospasm with an emphasis on recognition and management with the aim to increase awareness and improve treatment outcomes.